Soil solarization as a non-chemical weed control method in tree nursery production systems of the Pacific Northwest, USA - Wada, Nami; Berry, Pete A.; Hill, Brian; Mallory-Smith, Carol; Parke, Jennifer L. (Frontiers in Agronomy, 2024)
Soil solarization can be used to reduce the weed seedbank by trapping solar energy under clear plastic film where imbibed weed seed and seedlings can be killed by high soil temperatures. Field studies were conducted in the Pacific Northwest, USA, at three commercial tree nurseries to assess soil solarization to reduce the naturally occurring weed seedbank, and the time required to hand weed fields. Soil solarization was particularly effective in reducing the emergence of naturally occurring weeds in the fall and winter, when weed emergence was reduced by 94-96%. Emergence was reduced 67-81% during the subsequent spring and early summer. Nine to ten months after solarization, solarized areas had a 52 – 69% reduction in hand weeding time compared to non-solarized areas. Further field and laboratory tests were conducted with five weed species: Poa annua, Polygonum pensylvanicum, Amaranthus retroflexus, Portulaca oleracea, and Cyperus esculentus. Weed seeds and tubers were buried in packets at 5 and 10 cm to determine their viability after 6 weeks of solarization. Seed mortality differed by location and depth, with P. annua and P. pensylvanicum having the greatest percent seed mortality followed by A. retroflexus and variable results for P. oleracea and C. esculentus. A laboratory study was conducted with all but C. esculentus to quantify the exposure time at 45, 50, and 55 °C required for 90% death (T_90). Seed mortality differed depending on species and temperature; however, at 55 °C, there was a relatively rapid drop in seed viability for all species, and T_90 values ranged from 1.2 to 41 h whereas at 45 °C the range was 47 to > 3000 h. Similar to the field studies, P. annua and P. pensylvancium were more sensitive to heat, followed by A. retroflexus and P. oleracea. Results suggest that soil solarization can be an effective weed management tool in reducing the weed seedbank in Pacific Northwest nurseries with fall-sown crops but may not work for certain deeply rooted, thermotolerant weed species such as C. esculentus.